Eobathynella gwangjuensis sp. nov., a new species of Parabathynellidae (Crustacea, Bathynellacea) from South Korea - Ji, Su-Jung; Min, Gi-Sik (Zootaxa, 2022)
A new species of Parabathynellidae (Crustacea, Bathynellacea) was found in the interstitial groundwater of the Yeongsangang River in South Korea. The new species belongs to the genus Eobathynella Birstein and Ljovuschkin, 1964, which previously comprised six species, including two from South Korea. Eobathynella gwangjuensis sp. nov. can be distinguished from its congeners by the absence of setae on the last segment of the thoracopod endopods and by the presence of three finger-like setae on the exopod of male thoracopod VIII. In addition, we present gene sequences of the nuclear 18S rDNA and the mitochondrial cytochrome c oxidase subunit 1 of the new species, which was used to infer phylogenetic relationships with closely related species.